Konsep adi luhung sejarah kebudayaan Islam di Indonesia dan strategi pengembangannya - Nata, Abuddin (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Indonesia, with a majority Muslim population, presents consequences where Islamic teachings influence the life of the nation. As a religion that is perfect (al-kamilah), comprehensive (al-syamilah), balanced (al-tawazun) and moderate (al-tasawuth), Islam includes religious (al-diniyah) and worldly (al-muamalah) aspects, which complement each other. In the development of worldly aspects, Islam encourages cultures based on its teachings, creating interaction and healthy competition (fastabiqul khairat) with other cultures, such as Greece, China, India and Persia. This process is also seen in Indonesia, a pluralistic country with diverse cultures and customs. The relationship between Islam and local culture often results in harmony, assimilation or tension, as in West Sumatra during the pre-independence period. This paper, drawing on the Qur'an, Hadith, Islamic cultural history and scholarly observation, explores the prominence of Islamic culture, particularly in the arts, and its impact in Indonesia. The findings are relevant for building a more advanced future for Islam and Indonesia, based on the harmony between Islamic teachings and the characteristics of Indonesia's pluralistic society. Abstrak Indonesia, dengan mayoritas penduduk Muslim, menghadirkan konsekuensi di mana ajaran Islam memengaruhi kehidupan bangsa. Sebagai agama yang sempurna (al-kamilah), komprehensif (al-syamilah), seimbang (al-tawazun), dan moderat (al-tasawuth), Islam mencakup aspek keagamaan (al-diniyah) dan duniawi (al-muamalah), yang saling melengkapi. Dalam pengembangan aspek duniawi, Islam mendorong kebudayaan yang berbasis ajarannya, menciptakan interaksi dan kompetisi sehat (fastabiqul khairat) dengan kebudayaan lain, seperti Yunani, Cina, India, dan Persia. Proses ini juga terlihat di Indonesia, negara pluralistik dengan beragam budaya dan adat istiadat. Hubungan antara Islam dan budaya lokal sering menghasilkan harmoni, asimilasi, maupun ketegangan, seperti di Sumatera Barat pada masa pra-kemerdekaan. Makalah ini, dengan sumber al-Qur'an, Hadis, sejarah kebudayaan Islam, dan pengamatan ilmiah, mengeksplorasi keunggulan kebudayaan Islam, khususnya di bidang seni, serta dampaknya di Indonesia. Temuan ini relevan untuk membangun masa depan Islam dan Indonesia yang lebih maju, berlandaskan harmoni antara ajaran Islam dan karakteristik masyarakat pluralistik Indonesia.